Designers as change agents in the Circular Economy - Fleischmann, Katja (My University, 2020)
Several global reports have concluded that natural resource extraction at its current levels is unsustainable and will lead to rapid erosion of the environment and tax global economic growth. One of the alternative paradigms to conserve those resources is the Circular Economy, a system driven by innovation that extends the utility of products as long as possible through a series of strategies that re-use resources. Design can act as a bridging tool and a catalyst for the innovation demanded by the Circular Economy because of its flexibility as a problem-solving discipline. The intermediary role of design can adapt to the complex requirements of Circular Economy stakeholders who want to shift their way of doing business to a more sustainable model, despite formidable policy, economic, cultural and political obstacles. The author explores the evolution and utility of design from a discipline that shapes objects to one that constructs and facilitates complex systems of interactions among collaborators, which in the Circular Economy includes consumers, manufacturers, logistics companies, governments, business and science entrepreneurs. Several examples of design’s role in this facilitative process are presented that showcase the power of design to drive social and cultural transformations and re-cast industrial and business processes. Sustainable innovation is the centrepiece of the Circular Economy and design has a significant role to play in its adoption, particularly from a human-centred perspective that can address formidable constraints to its implementation.
Keywords: Democratisation of design; Co-creation; Circular Economy; Design-led innovation; Service design; Citizen designer; Sustainable innovation